HYDROGEL NANOCOMPOSITES FOR THE DIAGNOSIS AND TREATMENT OF CANCER - Samoylenko, O.A.; Kernosenko, L.O.; Samchenko, Yu.M.; Reznichenko, L.S.; Shlyakhovenko, V.O. (Reports of the National Academy of Sciences of Ukraine, 2024)
The methods of synthesis of hydrogel nanocomposites with incorporated gold nanoparticles and acid-activated Laponite® for early diagnosis and treatment of cancer were developed. The structure of the synthesized hybrid materials was confirmed by IR spectroscopy, and their properties were characterized by laser correlation spectroscopy, UV spectroscopy, zymography, etc. It has been shown that hybrid polymer systems based on polyvinylformal, gold nanoparticles and pH-sensitive hydrogels can be used to fill postoperative cavities with simultaneous targeted release of incorporated Albucid bacteriostatic. Acid modification of Laponite® results in nanoparticles with a monomodal size distribution and a diameter of about 150 nm, which in combination with polyacrylamide gel demonstrated high efficiency in electrophoretic separation of peripheral blood plasma proteins for early diagnosis of colorectal cancer.